Numerical review of Jones-Wilkins-Lee parameters for trinitrotoluene explosive in free-air blast - Giam, Anthoni (2022)
The analysis of complex blast scenarios typically requires advanced computational methods such as multi-material Eulerian and coupled Eulerian-Lagrangian (CEL) analysis where Jones-Wilkins-Lee (JWL) equation of state is used to model the explosive material. While multiple sets of empirical JWL parameters for trinitrotoluene (TNT) explosives have been published over the past few decades, there is also a lack of guidelines and comparative studies on their applications for the blast analysis. A standardized description of the explosive material behavior allows for a better interpretation of results from research studies involving different blast scenarios and JWL parameters. In this paper, the authors utilize numerical finite element (FE) simulations to investigate the influence of different TNT JWL parameter sets on the blast wave characteristics of a free-air blast across different scaled distances. Utilizing multi-material Eulerian analysis, a series of spherical free-air blasts involving a 100-kg TNT charge modeled with different TNT JWL parameters are conducted. The blast wave characteristics including the incident overpressure, impulse, and time of arrival (TOA) are benchmarked against the empirical-based Kingery-Bulmash air blast formulations through the conventional weapon effect calculator CONWEP. It was found that the incident overpressure and impulse are highly sensitive to the JWL parameters, with differences as high as 40% at smaller scaled distances, while the influence on TOA is much less significant. This paper hopes to provide a guide for future users on the appropriate JWL parameter sets to model the air blast events involving TNT explosives.